How do you find the derivative of sqrt(2x-3)√2x−3? Calculus Basic Differentiation Rules Chain Rule 1 Answer Mauricio M. Apr 18, 2018 f'(x) = 1/(sqrt(2x-3)) Explanation: f(x) = sqrt(2x-3) f'(x) = 1/(2sqrt(2x-3))*2 f'(x) = 1/(cancel2sqrt(2x-3))*cancel2 f'(x) = 1/(sqrt(2x-3)) Answer link Related questions What is the Chain Rule for derivatives? How do you find the derivative of y= 6cos(x^2) ? How do you find the derivative of y=6 cos(x^3+3) ? How do you find the derivative of y=e^(x^2) ? How do you find the derivative of y=ln(sin(x)) ? How do you find the derivative of y=ln(e^x+3) ? How do you find the derivative of y=tan(5x) ? How do you find the derivative of y= (4x-x^2)^10 ? How do you find the derivative of y= (x^2+3x+5)^(1/4) ? How do you find the derivative of y= ((1+x)/(1-x))^3 ? See all questions in Chain Rule Impact of this question 4974 views around the world You can reuse this answer Creative Commons License